Research on the Impact of Sex Ratio Changes on the Population Dynamics of Lamprey Based on the Lotka-Volterra Algorithm - Cheng, Binglin; Wang, Wenchao; Lei, Xiaohao; Ma, Suien (Transactions on Computer Science and Intelligent Systems Research, 2024)
This study employs mathematical modeling to investigate the impact of sex ratio changes on the sea lamprey population dynamics. Utilizing differential equations and specific models for population growth, reproduction success, and resource utilization efficiency, the study examines the effects of sex ratio on population dynamics, reproduction success rates, and resource usage efficiency. Diagrams illustrating variations in sex ratio and population quantities offer insights into their effects on population growth and ecological dynamics. The findings suggest that altering the sex ratio significantly influences reproductive success, resource efficiency, and overall ecosystem dynamics, potentially leading to changes in reproduction rates, population structure, genetic diversity, and predator-prey relationships. By analyzing the boosted Lotka-Volterra model, the study demonstrates that as the sex ratio effect (alpha) increases, significant fluctuations occur in prey populations, contributing to environmental instability. Moreover, predator populations exhibit greater variations and a sharp decline, indicating the intricate interaction between sex ratio, prey stability, and ecosystem dynamics. The conclusion is that changes in sex ratio have a significant impact on the ecosystem. Possible issues that might arise include changes in reproduction rate and population growth rate, changes in population structure, reduced genetic diversity, and changes in predator-prey relations. These results highlight the critical role of sex ratio in population dynamics and ecosystem stability, emphasizing the need for further exploration and management strategies in marine ecosystems.